The European Union and its eastern neighbourhood : Europeanisation and its twenty-first-century contradictions - Mannin, Mike; Flenley, Paul (Manchester International Relations, 2018)
This volume is timely in that it explores key issues which are currently at the forefront of the EU's relations with its eastern neighbours.